Attitudes of the generation x and y nurses working at psychiatry clinic towards individuals with alcohol-drug addiction and mental disorders - Büyükbayram, Ayşe; Baysan Arabacı, Leyla; Arabacıoğlu, İlkay (Journal of Dependence, 2017)
Objective: This study was conducted to determine attitudes of generations X and Y nurses working at psychiatry clinics towards alcohol-drug addiction and mental illnesses. Material and Method: This descriptive study was conducted with a total of 103 nurses. Data was collected using,“Introductory Information Form”,“Beliefs towards Mental Ilness Scale(BMI)”and“Attitude Scale(AS)”. Results: 72.8% of the nurses were Generation X and 27.2% were Generation Y. No statistically significant difference was found between Generation X and Y nurses with regard to mean scores of BMI total scale and subscales and AS. Conclusion: The attitudes of the X and Y generation nurses working in psychiatric units towards individuals who have a diagnosis of psychiatric disorder are positive while attitudes towards dependent individuals are negative, and nurses are affected by many factors. Moreover, the attitudes of the Y generation nurses to the individuals with mental disorders are more negative than those of the X generation, whereas their attitudes towards the dependent individuals are more positive.